Tunneling current via dislocations in InAs and InSb infrared photodiodes - Sukach, A.V.; Tetyorkin, V.V.; Krolevec, N.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
Carrier transport mechanisms are investigated in InAs and InSb infrared
photodiodes. The photodiodes were prepared by thermal diffusion of Cd and ion
implantation of Be into InAs and InSb single-crystal substrates of n-type conductivity,
respectively. The direct current was measured as a function of bias voltage and
temperature. The excess tunneling current is observed in the investigated photodiodes at
small forward bias voltages. Experimental proofs are obtained that dislocations are
responsible for this current. A model for the tunneling current via dislocations is briefly
discussed.